Inactivation or inhibition of AcrAB-TolC increases resistance of carbapenemase-producing Enterobacteriaceae to carbapenems. (5th March 2016) - Saw, Howard T. H.; Webber, Mark A.; Mushtaq, Shazad; Woodford, Neil; Piddock, Laura J. V.
Abstract: Objectives: The objective of this study was to study the contribution of the multidrug resistance AcrAB-TolC efflux system to carbapenem resistance in carbapenemase-producing Enterobacteriaceae and the impact of the efflux inhibitor PABN on this resistance. Methods: Klebsiella pneumoniae, Escherichia coli, Salmonella enterica serovar Typhimurium and their corresponding AcrAB-TolC mutants, each carrying carbapenemase-carrying plasmids (pKpQIL-UK with bla KPC and pNDM-HK with bla NDM ), were tested for their susceptibility to six β-lactam antibiotics according to the BSAC agar dilution method. MICs were also determined in the presence of efflux inhibitors. The susceptibility of ertapenem in the presence of 25 and 100 mg/L PABN was also determined for 86 non-replicate clinical isolates of carbapenemase-producing Enterobacteriaceae with OXA-48-like ( n  = 18), IMP ( n  = 12), VIM ( n  = 16), NDM ( n  = 20) or KPC ( n  = 20) enzymes. Outer membrane protein profiles were determined with SDS–PAGE. Results: The carbapenemase-producing AcrAB mutants of K. pneumoniae and E. coli and the TolC mutant of Salmonella Typhimurium had elevated resistance to carbapenem antibiotics. In Salmonella Typhimurium, the increase in carbapenem MIC correlated with the loss of OmpF. Sixty-two (72%) of the clinical isolates tested were also more resistant to ertapenem in the presence of PABN. SDS–PAGE showed that the presence of PABN affected outer membrane porin production, which was associated with the increased MIC values of ertapenem. Conclusions: The decreased susceptibility to carbapenems of carbapenemase-producing Enterobacteriaceae in the absence of AcrAB or TolC and/or in the presence of an efflux inhibitor (e.g. PABN) is likely due to the changes in porin expression (e.g. OmpF). Efflux inhibitors may not potentiate carbapenem activity, but rather could increase levels of resistance in carbapenemase-producing organisms.